Relationship between job satiseaction and psychological health among female employees at Ministry of Youth and Sports, Putrajaya / Nur Syahirah Rosli - Rosli, Nur Syahirah (2018)
The aim of this study is to examine the relationship between job satisfaction and psychological health among female employees at Ministry of Youth and Sports, Putrajaya. The data will be collected by using questionnaires. This sample of this study consisted of 175 female employees at Ministry of Youth and Sports, Putrajaya. Job satisfaction will be assessed by using the Job Satisfaction Survey (JSS; Spector, 1985) and psychological health will be assessed by using the General Health Questionnaire 28 (GHQ; Goldberg 1978). There are 2 statistical analyses which are descriptive statistics and inferential statistics. Descriptive statistics will be used for assessing the percentages, mean, mode and standard deviation and inferential statistics, Spearman Correlation will be used to identify whether there is any relationship job satisfaction and psychological health. The result of this study show that there is a signiTicant relationship between job satisfaction and psychological health among female employees at Ministry of Youth and Sports, Putrajaya. Job satisfaction and psychological are important causes of employee’s health. When employees are satisTied with their job, they are more productive and tend to be healthier and it could be a vice versa.